1997
DOI: 10.1017/s0143385797060987
|View full text |Cite
|
Sign up to set email alerts
|

Invariant measures of full dimension for some expanding maps

Abstract: It is an open problem to determine for which maps $f$, any compact invariant set $K$ carries an ergodic invariant measure of the same Hausdorff dimension as $K$. If $f$ is conformal and expanding, then it is a known consequence of the thermodynamic formalism that such measures do exist. (We give a proof here under minimal smoothness assumptions.) If $f$ has the form $f(x_1,x_2)=(f_1(x_1),f_2(x_2))$, where $f_1$ and $f_2$ are conformal and expanding maps satisfying $\inf \vert Df_1\vert\geq\sup\vert Df_2\ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 6 publications
4
85
0
1
Order By: Relevance
“…Consider y ∈ X such that π(y) ∈ [2 n 1] and z ∈ X such that π(z) = 2 ∞ . Then (6) and the fact that (S n ϕ)(z) = 0 for all n, and var n (S n ϕ) is not bounded. This is a contradiction.…”
Section: Proof Of (2)(d) and (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…Consider y ∈ X such that π(y) ∈ [2 n 1] and z ∈ X such that π(z) = 2 ∞ . Then (6) and the fact that (S n ϕ)(z) = 0 for all n, and var n (S n ϕ) is not bounded. This is a contradiction.…”
Section: Proof Of (2)(d) and (E)mentioning
confidence: 99%
“…Shin [18] showed that if there is a saturated compensation function G • π (see page 5 for the definition for the factor map π), then for any α > 0 the set of all shift-invariant measures µ on X that maximize h µ (σ X ) + αh πµ (σ Y ) is the set of equilibrium states for the function (α/(α + 1))G • π. A saturated compensation function helps us make some progress on the problem, giving us a systematic way to approach the problem (see pages 5,6, and 6). We will answer questions about SFT-NC carpets for which a saturated compensation function exists (when they are represented in symbolic dynamics, see page 6).…”
Section: Introductionmentioning
confidence: 99%
“…The smoothness C 1+γ was recently relaxed to C 1 [9]. An estimate from above for the Hausdorff dimension of compact invariant sets for differentiable maps has been given by A. Douady and J. Oesterlé [5], and by Ledrappier [11].…”
Section: Introductionmentioning
confidence: 99%
“…[Bow79], [Rue82], [Fal89], [Bar96], [GP97] and our introduction. It seems to be the first time that it is stated in the above generality.…”
Section: Random Julia Sets and Their Dimensionsmentioning
confidence: 99%